Revealing Fifth-Grade Students’ Understanding of the Universe - Coştu, Fatma; Özdemir, Nesibe Firdevs; Coştu, Bayram (Mimbar Sekolah Dasar, 2022)
Previous research has shown that students at almost all levels have misconceptions about both the shapes and sizes of celestial bodies in space. This study is essential to conduct on the students who take space topic in their schools for the first time This study aims at revealing fifth-grade students’ alternative conceptions about the size of the sun, earth, and moon and their relative positions to each other. This study employs action research by using a forced questionnaire and interview were used as the research instruments and involved 78 fifth-grade students as participants. To collect data, all students initially responded to a forced question questionnaire. Then, based on their responses, four students were chosen to be interviewed to clarify their alternative conceptions. The data analysis was carried out using interview and questionnaire data to reveal understanding and alternative conceptions of students’ responses. The results found that students had alternative conceptions of the earth’s shape in their minds. Moreover, alternative conceptions are commonly found in the sun, earth and moon positions.